2003
DOI: 10.1002/eat.10137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of group and individual cognitive‐behavioral therapy for patients with bulimia nervosa

Abstract: This has implications for the delivery of cost-effective and clinically effective treatment for BN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 13 publications
5
59
0
4
Order By: Relevance
“…We found significant differences in favor of IND, in terms of expert ratings of both binge eating and compensatory behaviors, at the 2.5-year follow-up. This result is in line with Chen et al 5 who showed that group CBT is slower than individual CBT in producing abstinence from bulimic behavior. One explanation for the advantage of IND over GRP could be that individual treatment, although based on manualbased treatment, can more easily be tailored to the specific needs of the individual patient.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We found significant differences in favor of IND, in terms of expert ratings of both binge eating and compensatory behaviors, at the 2.5-year follow-up. This result is in line with Chen et al 5 who showed that group CBT is slower than individual CBT in producing abstinence from bulimic behavior. One explanation for the advantage of IND over GRP could be that individual treatment, although based on manualbased treatment, can more easily be tailored to the specific needs of the individual patient.…”
Section: Resultssupporting
confidence: 93%
“…[1][2][3][4] A recent study by Chen et al 5 compared individual cognitive-behavioral therapy (CBT) with group CBT for BN and found that the effects of both treatments were equivalent by most measures, except for binge eating at posttreatment; participants in IND were significantly more abstinent. They also found dropout rates (defined as not attending treatment or assessment, or not responding to three telephone calls and a personal letter) to be similar in IND and GRP.…”
Section: Introductionmentioning
confidence: 97%
“…Vor diesem Hintergrund überrascht es nicht, dass die Unzufriedenheit mit der eigenen Figur eine zentrale Outcome-Variable in wichtigen Therapiestudien zur Bulimia nervosa [Chen et al, 2003], zur Anorexia nervosa [McIntosh et al, 2005] und auch zur Binge-EatingStörung [Grilo et al, 2005] [Anderson et al, 2004], ist der Body Shape Questionnaire (BSQ) [Cooper et al, 1987] [Fassino et al, 2002], Schwedische [Ghaderi und Scott, 2004] oder Französische [Rousseau et al, 2005]. Waadt et al [1992] Pook/Brähler/Tuschen-Caffier…”
Section: Schlüsselwörterunclassified
“…Die Autoren zeigten auf, dass durch die störungsspezifische Behandlung nicht nur eine Verbesserung der Essstörungssymptomatik er- reicht werden kann, sondern auch komorbide Symptome, die häufig mit einer BN einhergehen, reduziert werden können. Chen et al [2003] zeigten in einer kontrolliert randomisierten Vergleichsstudie für Gruppen-und Einzeltherapie mit KVT bei BN geringe bis sehr gute Effektstärken in den Essstörungsskalen (Tab. 1).…”
Section: Introductionunclassified